2011
DOI: 10.1002/etc.424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil metal contamination on glyphosate mineralization: Role of zinc in the mineralization rates of two copper-spiked mineral soils

Abstract: A systematic investigation into lowered degradation rates of glyphosate in metal-contaminated soils was performed by measuring mineralization of [(14)C]glyphosate to (14)CO(2) in two mineral soils that had been spiked with Cu and/or Zn at various loadings. Cumulative (14)CO(2) release was estimated to be approximately 6% or less of the amount of [(14)C]glyphosate originally added in both soils over an 80-d incubation. For all but the highest Cu treatments (400 mg kg(-1)) in the coarse-textured Arkport soil, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In this sense, both glyphosate and phosphate have the same average net charge when adsorbed to the soil with the highest affinity which, according from the values of the relevant pKa, correspond to a pH 6 and 8, respectively. This result is in agreement with numerous publications that show that inorganic phosphate forms mostly bidentate bonds to an oxide surface (Kwon & Kubicki, 2004; Kim et al, 2011; Li et al, 2013; Wang et al, 2013) being possible to relate the adsorption with the concentration of divalent phosphate ions in solution (Bowden et al, 1980).…”
Section: Discussionsupporting
confidence: 92%
“…In this sense, both glyphosate and phosphate have the same average net charge when adsorbed to the soil with the highest affinity which, according from the values of the relevant pKa, correspond to a pH 6 and 8, respectively. This result is in agreement with numerous publications that show that inorganic phosphate forms mostly bidentate bonds to an oxide surface (Kwon & Kubicki, 2004; Kim et al, 2011; Li et al, 2013; Wang et al, 2013) being possible to relate the adsorption with the concentration of divalent phosphate ions in solution (Bowden et al, 1980).…”
Section: Discussionsupporting
confidence: 92%
“…Yang et al [69] showed that urea was inhibited by 75.1% with the presence of Cd (100 mg/kg) and Pb (500 mg/kg) in a controlled experiment. Kim et al [70] found inhibitions from 21.5…”
Section: Respiration and Enzyme Activitiesmentioning
confidence: 97%
“…However, it was until now unknown the implications of simultaneous exposures of copper and pesticides and the potential deleterious effects on the dissipation efficiency of the biomixture. The above-mentioned aspect is a key parameter, because it has been shown that copper can cause a negative impact on pesticide dissipation in soil (Gunasekara et al, 2005;Gaw et al, 2006;Liu et al, 2007;Kim et al, 2011;Dewey et al, 2012). In this regard, Dewey et al (2012) reported that ATZ degradation in a sandy loam agricultural soil was adversely affected by copper sulfate at 100 or 1000 mg kg −1 .…”
Section: Pesticide Dissipationmentioning
confidence: 99%
“…Among them, copper oxychloride (Ox) is annually applied to control several plant diseases (Nel et al, 1999). Nevertheless, copper tends to accumulate in surface layers of soil (Rusjan et al, 2007;McBride et al, 1981), which may eventually exert adverse eco-toxicological effects including interference on production and enzyme functionality of soil microorganisms (Gadd et al, 2001;Wang et al, 2009;Wightwick et al, 2010) and the decrease in pesticide degradation ability of soils at high copper levels (Jindal et al, 2000;Gunasekara et al, 2005Gaw et al, 2006Liu et al, 2007;Kim et al, 2011). In this context, Kunito et al (1999) and Viti et al (2008) reported that a copper concentration of 100 mg kg −1 produced alterations in microbial communities.…”
Section: Introductionmentioning
confidence: 99%